(untitled) (International Journal of Engineering and Computer Science, 2014)
The ability to track, trace and control anything by anyone from anywhere on the planet has been mankind’s unfulfilled desire. The usefulness of GSM and GPS has made them popular in their own context; integrating these technologies can prove to be a flamboyant solution for many unsolved problems. The idea of this paper is to integrate these two technologies into one system and provide an effective application for vehicle tracking as well as personal tracking. To implement a multi tracking system use of the following two technologies can be made, firstly GSM(Global System for Mobile) which is a set of standards to describe technologies for Second Generation (2G) and GPS(Global Positioning System) which is a satellite-based navigation system consisting several satellites revolving around the earth. The system will provide solution for tracking and tracing of multiple movable objects at a same time, so the name Multi-Tracking System. We can see the current location of the object and other add-on features, for vehicles there will be live tracing and tracking via GPS, controlling its subsystem parts via GSM network using SMS or GPRS. The whole system will be implemented in Microsoft .Net Technology, for system components C#.net will be used and for web based parts ASP.net will be used.